The determinants of stock market performance United States of America (USA) / Mohammad Afifuddin Mat Daud - Mat Daud, Mohammad Afifuddin (2019)
This paper is to identify the factor that affect the determinants of stock market performance in united states of America (USA) from the year 2010 until 2017 which contain a monthly data set of 96 observations. The issues that have been questioned here is does the macroeconomic variable influence the stock market performance, what are the significant variable that influence stock market and relationship between macroeconomic variable in long run relationship. This paper using ordinary least square method (OLS) in order to get the final result. For the diagnostic checking, there no multicollinearity problem detected in this paper. The result indicates that all variables are export, oil price, interest rate and gold price are significant in this study, the most significant variable is export and base on long run equation researcher get that three variables at level significant 0.01 and one variable at level significant 0.05. what researcher can conclude is this research is all objective is achieve and useful for further researcher.